Roles and mechanisms of garlic and its extracts on atherosclerosis: A review - Li, Min; Yun, Wingyan; Wang, Guibin; Li, Anqi; Gao, Jing; He, Qingyong (Frontiers in Pharmacology, 2022)
The prevention and treatment of cardiovascular diseases (CVDs) have achieved initial results, but the number of CVDs patients will increase rapidly in the next 10 years. Atherosclerosis (AS) is a significant risk factor for CVDs. The impact of lifestyle and daily diet varies considerably between different countries and continents and has been shown to affect the development of various diseases such as diabetes and CVDs. Primary and secondary prevention using alternative supplements and methods to avoid or reduce the use of traditional pharmacological drugs have also become popular. One of the reasons for this is that pharmacological drugs with lipid-lowering, and blood pressure-lowering effects cause many side effects that may negatively impact the quality of life. Patients are now emphasizing reliance on lifestyle changes to reduce cardiovascular risks. Garlic is a medicinal and edible Chinese herbal medicine with an extended application history. In this study, by reviewing the latest domestic and international studies, the antiatherogenic effects of garlic are eximious. And the mechanisms are mainly related to hypolipidemic, antioxidant, antithrombotic, inhibiting angiogenesis, protecting endothelial cells, anti-inflammatory, anti-apoptotic, inhibiting vascular smooth muscle proliferation, and regulating gut microbiota. The main signaling pathways involve AMPK/TLRs, Keap1/Nrf2, PI3K/AKT, PPARγ/LXRα, GEF-H1/RhoA/Rac, etc. The antiatherogenic effect and molecular mechanism of garlic were reviewed in this study to obtain a robust evidence basis for the clinical application and mechanistic study and provide a theoretical basis for further utilization of garlic.